A Pd-catalyzed direct entry to 11-substituted 6H-isoindolo[2, 1-a]indol-6-one derivatives as potential anticancer agents. Issue 108 (19th October 2015) - Nallapati, Suresh Babu; Adepu, Raju; Ashfaq, Mohd Ashraf; Sreenivas, B. Yogi; Mukkanti, K.; Pal, Manojit
Abstract : 11-Substituted 6 H -isoindolo[2, 1- a ]indol-6-ones are prepared via a sequential intramolecular Heck reaction of dihalo N -allyl substituted N -arylbenzamide derivatives. Abstract : We describe Pd-mediated one-step synthesis of 11-substituted 6 H -isoindolo[2, 1- a ]indol-6-ones via a sequential intramolecular Heck reaction of the corresponding dihalo N -allyl substituted N -arylbenzamide derivatives. Several of these compounds showed promising antiproliferative properties when tested against a number of cancer cell lines in vitro .